Formation of brood fish shoals from farmed breeders ( Phase 1: Biotechnique of Beluga (Huso huso) Rearing in Freshwater) - Mohseni, Mahmoud; Bahmani, M.; Pourali, H.; Kazemi, R.; Aghtoman, V.; Pourkazemi, M. (Iranian Fisheries Science Research Institute, 2005)
The present study was conducted to determine ideal diets for the commercial culture of beluga under rearing conditions. The objective of this study was to determine optimum protein levels in adaptation, growth and maintenance diets used in the four study phases. In the first phase 2400 beluga larvae with an average weight of 400-700 mg were stocked at a density of 200 larvae m-2 . Four treatments were used and four replicates run for each treatment. On the basis of results obtained, larvae in Treatment A showed highest growth (P<0.05). In the second phase, beluga specimens with an initial weight of 4.3 ± 0.14 g were studied for a period of 139 days in a random block design and were fed three different experimental diets at a rate of 2-3 % of their body weight. Three replicates were used for each treatment. Percentage body weight increase (% BWI), FCR, SGR and growth rates were significantly influenced by the protein content of the diets used (P<0.05). On the basis of Analysis of variance and Tukey Test conducted on results obtained the protein requirement for beluga in the 5-50 g weight class is about 50 %, and with an increase in body weight to about 120 g the protein requirement decreases to 45 %. Therefore diets can be formulated from good quality protein sources 45-50 % crude protein to achieve maximum growth in juvenile hatchery reared beluga. In the third phase 130 day old beluga specimens with an average body weight of 95 ± 1.2 g were reared for a period of 110 days on five experimental diets (three replicates run for each treatment) containing 40-50 % protein and similar levels of fat and energy. In the forth phase 240 day old specimens with an average body weight of 453.3 ± 8.3 g were reared on three experimental diets (ideal diets determined from first phase) (three replicates run for each treatment) for a period of 120 days. Diets were fed four times a day at 1.5 2 % of body weight. It is evident from the comparison of mean values in different treatments studied that different levels of protein ...